A Case of Unresolving Pneumonia. (18th June 2016) - Hosokawa, Sawako Kaku; Yamamoto, Shuhei; Kataoka, Yuki; Shimizu, Taro
Abstract : A 33‐year‐old woman was transferred to our hospital for an unresolving pneumonia, who initially presented with dyspnea. Initially antibiotic therapy was started under the suspicion of community‐acquired pneumonia, however, her respiratory status worsened at the previous hospital. Computed tomography (CT) on presentation showed peripheral ground glass opacities in both sides of the upper lobe. Also despite additional prednisolone therapy, her respiratory status worsened. On admission to our hospital, physical examination showed Gottoron's sign in her right elbow. From the nature of the rash, the absence of myositis symptoms and rapid respiratory worsening, we suspected clinically amyopathic dermatomyositis (CADM). After the triple drug therapy, her respiratory status improved.